Towards accessible and personalized mobile learning for learners with disabilities - Madani, H.; Ayed, L.; Jemni, M.; Sampson, Demetrios (IEEE Computer Society, 2013)
The integration of mobile devices in education is a new quite, which is commonly referred to as Mobile Learning. Mobile learning aims to facilitate and improve learning strategies that exploit individual learners' context, so that, they can learn from anywhere and at anytime using mobile devices. In order to let learners with disabilities take benefits from mobile learning systems, we propose in this paper an accessible and personalized mobile learning system to learners with disabilities which aims to adapt the learning activities to the learner's needs and/or preferences according to his/her disability's group taking into account the changing mobile context during the learning process. © 2013 IEEE.